Src activation by β-adrenoreceptors is a key switch for tumour metastasis - Armaiz-Pena, Guillermo N.; Allen, Julie K.; Cruz, Anthony; Stone, Rebecca L.; Nick, Alpa M.; Lin, Yvonne G.; Han, Liz Y.; Mangala, Lingegowda S.; Villares, Gabriel J.; Vivas-Mejia, Pablo; Rodriguez-Aguayo, Cristian; Nagaraja, Archana S.; et al. (Nature Communications, 2013)
Noradrenaline can modulate multiple cellular functions important for cancer progression; however, how this single extracellular signal regulates such a broad array of cellular processes is unknown. Here we identify Src as a key regulator of phosphoproteomic signalling networks activated in response to beta-adrenergic signalling in cancer cells. These results also identify a new mechanism of Src phosphorylation that mediates beta-adrenergic/PKA regulation of downstream networks, thereby enhancing tumour cell migration, invasion and growth. In human ovarian cancer samples, high tumoural noradrenaline levels were correlated with high pSrcY419 levels. Moreover, among cancer patients, the use of beta blockers was significantly associated with reduced cancer-related mortality. Collectively, these data provide a pivotal molecular target for disrupting neural signalling in the tumour microenvironment.
Gesehen am 26.11.2020